Pengaruh Suhu dan Oksigen Terhadap Penetasan Telur dan Kelulushidupan Awal Larva Ikan Pawas (Osteochilus hasselti C.V.) - Junita Hutagalung; Hamdan Alawi; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on 24-30 May 2016 in the Laboratory Fish Hatchery and Breeding Faculty of Fisheries and Marine Science University of Riau. The purpose of this study are to determine the influence of temperature (room temperature and 30°C) and dose of aquamate (0 mg/L and 20 mg/L) on fertilization, hatching and larvae survival of Pawas (Osteochilus hasselti C.V.). The method used in this study is an experimental method by using a completely randomized design with 2x2x3 factorial design. The first factor is the temperature (room temperature and 30°C), while the second factor is the dose of aquamate (0 mg/L and 20 mg/L) with three replications. Fish kept in the twelve unit of 30x30x30cm aquarium with the volume of water were 15 L each.The result showed that the treatment of the giving different temperature and oxygen to hatching the eggs and 5 days fish larvae initial survival of Pawas (Osteochilus hasselti C.V.) that is best for Fertilization Rate (FR) of Pawas eggs is room temperature with the addition 20 mg/L aquamate which produce figure conception amounted to 43.78%, figure Hatching Rate (HR) amounted to 63.24%, the rate of Survival Rate (SR) amounted to 96%. Data from water quality measurements during the study that is the temperature used is room temperature and 30°C, pH range 6-8. The levels of dissolved oxygen on dose of aquamate 0 mg/L namely 3.0 mg/L while on dose of aquamate 20 mg/L namely 7.0 mg/L. Dissolved oxygen was increased on dose of aquamate 20 mg/L as much as 4 mg/L after one day the addition of aquamate into aquarium.Keywords: temperature, oxygen, fertilization rate, hatching rate, survival rate, Osteochilus hasselti C.V.